Medical terminology for dummies eaudiobook - Henderson, CMT-R, HRT, Beverley (Tantor Media, 2020)
Every job in the medical field needs some background in medical terminology. From the check-in desk to the doctor to the pharmaceutical sales rep, and everyone around and in between, healthcare professionals and those in adjacent fields use a common and consistent vocabulary to improve quality, safety, and efficiency. Medical Terminology For Dummies is a powerful resource for current and prospective healthcare professionals. It provides different ways to memorize the words and their meanings, including ideas for study materials, flash cards, quizzes, mind maps, and games. Plus, you'll discover how to identify, pronounce, define, and apply words in proper context. ● Grasp the standardized language of medicine ● Find the easiest way to remember tongue-twisting terms ● Benefit from lots of definitions and examples ● Understand, retain, and put this knowledge to use If you're one of the millions of professionals hoping to succeed in this booming field, this book gets you talking the talk so you can walk the walk!